2012
DOI: 10.4103/1658-354x.97021
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided single injection infraclavicular brachial plexus block using bupivacaine alone or combined with dexmedetomidine for pain control in upper limb surgery: A prospective randomized controlled trial

Abstract: Background:Dexmedetomidine, is a selective α2-adrenoceptor agonist that is used as an adjuvant mixed with local anesthetics during regional anesthesia. This study was designed to test the efficacy of adding dexmedetomidine to bupivacaine during placement of infraclavicular brachial plexus blockade (ICB).Methods:Sixty adult patients were divided into 2 equal groups of 30 subjects each. Patients in Group I received an ICB using 30 mL of 0.33% bupivacaine and Group II patients received 30 mL of 0.33% bupivacaine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 24 publications
6
51
3
1
Order By: Relevance
“…Dexmedetomidine is highly selective (8 time more selective than clonidine),[ 7 ] specific and potent α 2 -adrenergic agonist having analgesic, sedative, antihypertensive, and anesthetic sparing effects when used in systemic route. [ 8 ] Adding dexmedetomidine to local anesthetics during peripheral nerve blockade[ 9 ] and regional anesthesia[ 10 ] procedures may also prove efficacious for the surgical patients. In human study, dexmedetomidine has also shown to prolong the duration of the block and post-operative analgesia when added to local anesthetic in various regional blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine is highly selective (8 time more selective than clonidine),[ 7 ] specific and potent α 2 -adrenergic agonist having analgesic, sedative, antihypertensive, and anesthetic sparing effects when used in systemic route. [ 8 ] Adding dexmedetomidine to local anesthetics during peripheral nerve blockade[ 9 ] and regional anesthesia[ 10 ] procedures may also prove efficacious for the surgical patients. In human study, dexmedetomidine has also shown to prolong the duration of the block and post-operative analgesia when added to local anesthetic in various regional blocks.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Similarly, Ammar and Mahmoud also found that significantly lower IV morphine (4.9 mg vs. 13.6 mg) was given as rescue analgesic in the bupivacaine plus dexmedetomidine group while comparing with plain bupivacaine group in infraclavicular brachial plexus block. [16]…”
Section: Discussionmentioning
confidence: 99%
“…However they did not found any consistently significant differences in blood pressures between the groups [24]. Amany S. Ammar et al in their clinical trial added dexmedetomidine to bupivacaine during placement of ultrasound guided infraclavicular block and they concluded that adding dexmedetomidine to bupivacaine enhanced onset and duration of sensory and motor block, prolonged duration of analgesia and yields lower VAS pain scores [25].…”
Section: Discussionmentioning
confidence: 93%